Unearthing LTR Retrotransposon gag Genes Co-opted in the Deep Evolution of Eukaryotes - Wang, Jianhua; Han, Guan-Zhu (Molecular biology and evolution, 2021)
LTR retrotransposons comprise a major component of the genomes of eukaryotes. On occasion, retrotransposon genes can be recruited by their hosts for diverse functions, a process formally referred to as co-option. However, a comprehensive picture of LTR retrotransposon gag gene co-option in eukaryotes is still lacking, with several documented cases exclusively involving Ty3/Gypsy retrotransposons in animals. Here, we use a phylogenomic approach to systemically unearth co-option of retrotransposon gag genes above the family level of taxonomy in 2,011 eukaryotes, namely co-option occurring during the deep evolution of eukaryotes. We identify a total of 14 independent gag gene co-option events across more than 740 eukaryote families, eight of which have not been reported previously. Among these retrotransposon gag gene co-option events, nine, four, and one involve gag genes of Ty3/Gypsy, Ty1/Copia, and Bel-Pao retrotransposons, respectively. Seven, four, and three co-option events occurred in animals, plants, and fungi, respectively. Interestingly, two co-option events took place in the early evolution of angiosperms. Both selective pressure and gene expression analyses further support that these co-opted gag genes might perform diverse cellular functions in their hosts, and several co-opted gag genes might be subject to positive selection. Taken together, our results provide a comprehensive picture of LTR retrotransposon gag gene co-option events that occurred during the deep evolution of eukaryotes and suggest paucity of LTR retrotransposon gag gene co-option during the deep evolution of eukaryotes.